Shareholders’ Preference for Corporate Renewable Energy Project Finance in Nigeria - Isa, Muhammad Aminu; Jibril, Rabiu Saminu; Salawudeen, Aishat (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
This study explores shareholders RE preferences (technology, cost, availability, and capacity) as a determinant of RE project finance during energy transition. The data for the study were generated from a sample of 400 shareholders of firms listed in the Nigeria Exchange Group (NGX) through a questionnaire survey. The Kruskal-Wallis’ estimation techniques were deployed to analyze the data and measure the convergence of shareholder preferences towards RE projects. The results suggest that shareholders have divergent preferences on energy cost across different technology capacities. Similarly, the results suggest that shareholders have divergent preferences on durability across different energy technologies. However, the shareholders showed convergent preferences on availability of energy resources irrespective of energy technology. These results have implications for corporate REF because shareholders assume significant role in corporate investment decisions. These novel findings suggest that shareholder’s preference is a significant determinant of REF. Therefore, policymakers should consider these preferences as a guide in reassessing, evaluating and reviewing energy transition plans, particularly those aspects that affect private investment.